ANALISIS PEMASARAN IKAN BANDENG (Chanos chanos) DI DESA BABULU LAUT, KABUPATEN PENAJAM PASER UTARA PROVINSI KALIMANTAN TIMUR - Listiowati; Elly Purnamasari; Helminuddin (2339-1324, 2017)
The purpose of this research is to determine marketing channel, instutional market, marketing margin, marketing effisiency, profit and milkfish marketing problems. Data collection was conducted with purposive and snowball sampling methods by using questionnaire spread to respondents. The research was conducted star from April 2016 to February 2017. Field data were analyze by descriptive quantitative using table and charts. The result showed that fish marketing channel consist of two levels type, namely, 0 level and the second level. Institutional market was involved in marketing are: Pondfarmers, wholesalers, and retailers. Margin of Marketing obtained by farmers, wholesalers, retailers, respectively Rp 2,000. The marketing process is efficient because each intermediary marketing gained share (part) above 50%. Gains derived by farmers on average Rp 93,169,617 / year, wholesaler’s profits by an average of Rp 38,544,933 / year, and the benefits retailers by an average of Rp 19,977,917 / year. Problems faced by pondfarmers in the research area are insufficient of natural food (klekap), the wholesalers often undertakes demand for milkfish from outside the area. For retailers if the price of milkfish is expensive was impact low purchasing power of consumers so that retailers loss.